The Biodiversity of Retreating Glaciers Leaves an Ecological Legacy in Emerging Soil Communities - Isabel Cantera; Silvio Marta; Alexis Carteron; Alessia Guerrieri; Simone Giachello; Aurélie Bonin; Roberto Ambrosini; Roberto Sergio Azzoni; Marco Caccianiga; Francesca Pittino; Andrea Simonicini; Barbara Valle; et al. (Global Change Biology, 2026)
Glacier retreat is transforming high‐mountain and polar landscapes, replacing ice with vast, newly exposed terrains where soil development and ecological succession start. Although ecosystems developing in deglaciated terrains are often viewed as starting from scratch, glaciers host diverse communities whose links with emerging soils remain unquantified. Using environmental DNA metabarcoding, we provide the first multi‐taxa assessment of biodiversity transitions across the supraglacial–proglacial interface across five glacier systems in Svalbard, the Alps and Patagonia. We analysed 212 samples from the surfaces of retreating glaciers and their forelands, spanning a chronosequence from 1 to 483 years since deglaciation. Recently deglaciated soils (≤ 10 years since glacier retreat) showed taxonomic and functional similarity to supraglacial communities. This ecological continuity was highly taxon‐specific, being pronounced for communities of microorganisms (Bacteria, Fungi, Protista) but weak for animals (e.g., Collembola, Insecta). For microbes, similarity diminished rapidly over succession as community turnover increased, and functional composition shifted from phototrophic and saprotrophic dominance toward heterotrophic and symbiotic assemblages. Shared microbial taxa and functions indicate a transient glacial influence during early soil succession. Our results suggest that early soil communities are not assembled independently of glacier ecosystems, but are initially linked to them through diverse ecological pathways that diminish over time. The observed glacier–proglacial connectivity challenges the view of succession on deglaciated terrains as beginning on lifeless substrates and instead points to a glacial legacy in emerging soils. As glaciers rapidly disappear under climate change, the unique biodiversity they host is also being lost, underscoring the urgent need to study supraglacial and proglacial systems together. Such integration is essential to understand ecological succession in proglacial ecosystems, which are expected to play an increasingly important role in this century.

Effects of local management and landscape factors on taxonomic and functional diversity of multiple taxa in managed grasslands - Matteo Conti; Andrea Dalpasso; Alberto Mattia Nodari; Isabel Cantera; Benedetta Barzaghi; Mattia Brambilla; Andrea Ferrari; Gentile Francesco Ficetola; Simone Giachello; Elia Lo Parrino; Valeria Messina; Carlo Polidori; et al. (Agriculture, Ecosystems & Environment, 2026)

Quantitative Metabarcoding Reveals the Effects of Ecological Factors and Invasive Species on Functional Diversity of Freshwater Insects - Elia Lo Parrino; Isabel Cantera; Alessia Guerrieri; Benedetta Barzaghi; Mattia Falaschi; Martina Muraro; Serena Pozzi; Raoul Manenti; Gentile Francesco Ficetola (Molecular Ecology, 2026)
Aquatic insects are the most biodiverse freshwater animals. DNA metabarcoding data are increasingly used to assess variation in insect communities, but they are rarely integrated with information on the abundance or biomass of different taxa that can provide key insights into their functional responses. Here, we combined organismal metabarcoding and biomass estimates of different clades of aquatic insects to assess how different facets of their biodiversity (taxonomic and functional diversity; species traits) are affected by multiple stressors, including invasive species, drought and variation in vegetation. In 44 waterbodies in Northern Italy, we measured environmental features (e.g., pond surface, hydroperiod, and the presence of the invasive crayfish Procambarus clarkii ) and collected insect specimens. Specimens were weighed and then used for DNA metabarcoding. The relationship between biomass of seven insect orders and their relative abundance in metabarcoding data was used to obtain quantitative estimates of taxa biomasses across communities and to extract multiple diversity measures. Different facets of biodiversity showed distinct responses to the environmental stressors. The taxonomic diversity of insect communities strongly responded to aquatic vegetation, while functional diversity was more sensitive to the invasive crayfish. Total insect biomass was negatively related to fish presence, but insects with different functional traits showed specific responses to environmental features. Our results show that integrating metabarcoding data with biomass estimates can improve our understanding of community responses to multiple stressors and highlight the importance of considering multiple measures of diversity to get a comprehensive assessment of aquatic insects' responses to environmental variation.

Describing functional diversity of communities from environmental DNA - Isabel Cantera; Simone Giachello; Tamara Münkemüller; Marco Caccianiga; Mauro Gobbi; Gianalberto Losapio; Silvio Marta; Barbara Valle; Krzysztof Zawierucha; Wilfried Thuiller; Gentile Francesco Ficetola (Trends in Ecology & Evolution, 2025)

Functional changes of protist communities in soil after glacier retreat - Simone Giachello; Isabel Cantera; Alexis Carteron; Aurelie Bonin; Alessia Guerrieri; Roberto Ambrosini; Marco Caccianiga; Mauro Gobbi; Silvio Marta; Gentile Francesco Ficetola (Science of The Total Environment, 2024)

Local climate modulates the development of soil nematode communities after glacier retreat - Alessia Guerrieri; Isabel Cantera; Silvio Marta; Aurélie Bonin; Alexis Carteron; Roberto Ambrosini; Marco Caccianiga; Fabien Anthelme; Roberto Sergio Azzoni; Peter Almond; Pablo Alviz Gazitúa; Sophie Cauvy‐Fraunié; et al. (Global Change Biology, 2024)
The worldwide retreat of glaciers is causing a faster than ever increase in ice‐free areas that are leading to the emergence of new ecosystems. Understanding the dynamics of these environments is critical to predicting the consequences of climate change on mountains and at high latitudes. Climatic differences between regions of the world could modulate the emergence of biodiversity and functionality after glacier retreat, yet global tests of this hypothesis are lacking. Nematodes are the most abundant soil animals, with keystone roles in ecosystem functioning, but the lack of global‐scale studies limits our understanding of how the taxonomic and functional diversity of nematodes changes during the colonization of proglacial landscapes. We used environmental DNA metabarcoding to characterize nematode communities of 48 glacier forelands from five continents. We assessed how different facets of biodiversity change with the age of deglaciated terrains and tested the hypothesis that colonization patterns are different across forelands with different climatic conditions. Nematodes colonized ice‐free areas almost immediately. Both taxonomic and functional richness quickly increased over time, but the increase in nematode diversity was modulated by climate, so that colonization started earlier in forelands with mild summer temperatures. Colder forelands initially hosted poor communities, but the colonization rate then accelerated, eventually leveling biodiversity differences between climatic regimes in the long term. Immediately after glacier retreat, communities were dominated by colonizer taxa with short generation time and r‐ecological strategy but community composition shifted through time, with increased frequency of more persister taxa with K‐ecological strategy. These changes mostly occurred through the addition of new traits instead of their replacement during succession. The effects of local climate on nematode colonization led to heterogeneous but predictable patterns around the world that likely affect soil communities and overall ecosystem development.

Toward a common set of functional traits for soil protists - Simone Giachello; Isabel Cantera; Alexis Carteron; Silvio Marta; Cristina Cipriano; Alessia Guerrieri; Aurélie Bonin; Wilfried Thuiller; Gentile Francesco Ficetola (Soil Biology and Biochemistry, 2023)

Metabarcoding data reveal vertical multitaxa variation in topsoil communities during the colonization of deglaciated forelands - Alessia Guerrieri; Alexis Carteron; Aurélie Bonin; Silvio Marta; Roberto Ambrosini; Marco Caccianiga; Isabel Cantera; Chiara Compostella; Guglielmina Diolaiuti; Diego Fontaneto; Ludovic Gielly; Fabrizio Gili; et al. (Molecular Ecology, 2023)
Ice‐free areas are expanding worldwide due to dramatic glacier shrinkage and are undergoing rapid colonization by multiple lifeforms, thus representing key environments to study ecosystem development. It has been proposed that the colonization dynamics of deglaciated terrains is different between surface and deep soils but that the heterogeneity between communities inhabiting surface and deep soils decreases through time. Nevertheless, tests of this hypothesis remain scarce, and it is unclear whether patterns are consistent among different taxonomic groups. Here, we used environmental DNA metabarcoding to test whether community diversity and composition of six groups (Eukaryota, Bacteria, Mycota, Collembola, Insecta, and Oligochaeta) differ between the surface (0–5 cm) and deeper (7.5–20 cm) soil at different stages of development and across five Alpine glaciers. Taxonomic diversity increased with time since glacier retreat and with soil evolution. The pattern was consistent across groups and soil depths. For Eukaryota and Mycota, alpha‐diversity was highest at the surface. Time since glacier retreat explained more variation of community composition than depth. Beta‐diversity between surface and deep layers decreased with time since glacier retreat, supporting the hypothesis that the first 20 cm of soil tends to homogenize through time. Several molecular operational taxonomic units of bacteria and fungi were significant indicators of specific depths and/or soil development stages, confirming the strong functional variation of microbial communities through time and depth. The complexity of community patterns highlights the importance of integrating information from multiple taxonomic groups to unravel community variation in response to ongoing global changes.

Environmental DNA reveals a mismatch between diversity facets of Amazonian fishes in response to contrasting geographical, environmental and anthropogenic effects - Opale Coutant; Céline Jézéquel; Karel Mokany; Isabel Cantera; Raphaël Covain; Alice Valentini; Tony Dejean; Sébastien Brosse; Jérôme Murienne (Global Change Biology, 2023)
Freshwater ecosystems are among the most endangered ecosystem in the world. Understanding how human activities affect these ecosystems requires disentangling and quantifying the contribution of the factors driving community assembly. While it has been largely studied in temperate freshwaters, tropical ecosystems remain challenging to study due to the high species richness and the lack of knowledge on species distribution. Here, the use of eDNA‐based fish inventories combined to a community‐level modelling approach allowed depicting of assembly rules and quantifying the relative contribution of geographic, environmental and anthropic factors to fish assembly. We then used the model predictions to map spatial biodiversity and assess the representativity of sites surveyed in French Guiana within the EU Water Framework Directive (WFD) and highlighted areas that should host unique freshwater fish assemblages. We demonstrated a mismatch between the taxonomic and functional diversity. Taxonomic assemblages between but also within basins were mainly the results of dispersal limitation resulting from basin isolation and natural river barriers. Contrastingly, functional assemblages were ruled by environmental and anthropic factors. The regional mapping of fish diversity indicated that the sites surveyed within the EU WFD had a better representativity of the regional functional diversity than taxonomic diversity. Importantly, we also showed that the assemblages expected to be the most altered by anthropic factors were the most poorly represented in terms of functional diversity in the surveyed sites. The predictions of unique functional and taxonomic assemblages could, therefore, guide the establishment of new survey sites to increase fish diversity representativity and improve this monitoring program.